Peer pressure, incentives, and gender: an experimental analysis of motivation in the workplace - Charles Bellemare; Patrick Lepage; Bruce S. Shearer (Institute for the Study of Labor (IZA), 2009)
We present results from a real-effort experiment, simulating actual work-place conditions, comparing the productivity of workers under fixed wages and piece rates. Workers, who were paid to enter data, were exposed to different degrees of peer pressure under both payment systems. The peer pressure was generated in the form of private information about the productivity of their peers. We have two main results. First, we find no level of peer pressure for which the productivity of either male or female workers is significantly higher than productivity without peer pressure. Second, we find that very low and very high levels of peer pressure can significantly decrease productivity (particularly for men paid fixed wages). These results are consistent with models of conformism and self-motivation.
urn:nbn:de:101:1-20090209182
Keywords: M52; C91; 330; Peer effects; fixed wages; piece rates; gender; Leistungsmotivation; Soziale Beziehungen; Leistungsorientierte Vergütung; Arbeitsproduktivität; Geschlecht; Test